A bibliometric analysis of sustainable digital transformation in developing countries' higher education - Omar, Abukar Mukhtar; Abdullahi, Mohamed Omar (Frontiers in Education, 2024)
The integration of digital technologies in higher education has revolutionized educational experiences, processes, and pedagogical methods, particularly in developing countries. Additionally, sustainability in education has become a critical focus, aligning with global efforts to promote sustainable development. This study conducts a comprehensive bibliometric analysis to investigate research trends and patterns in sustainable digital transformation (SDT) within higher education in the context of developing countries from 1991 to 2024. Employing the SCOPUS database, the analysis reveals a significant increase in publications on this topic, highlighting a growing scholarly interest. Key themes identified include digital transformation, innovation, sustainability, and technology-enhanced learning environments. Influential sources and journals contributing to this field are identified, with the Journal of Educational Technology & Society being the most cited. Collaboration networks among researchers are analyzed, showcasing the interconnectedness and interdisciplinary nature of this research area. Thematic evolution mapping indicates a shift from addressing challenges and barriers to exploring opportunities and benefits of digital transformation. The findings underscore the need for tailored approaches to address the unique socio-economic and cultural challenges faced by developing countries. This study fills a gap in the literature by providing a comprehensive overview of how SDT is being explored and implemented in higher education institutions in developing countries, offering insights into future research directions and practical implications for sustainable development in this sector.